UPAYA ORGANISASI BI-NATIONAL AMERICAN INDONESIAN EXCHANGE FOUNDATION (AMINEF) DALAM MENGENALKAN BUDAYA DAN BAHASA INDONESIA DI AMERIKA SERIKAT - Ailsa Adrina, (2023)
The collaboration between Indonesia and the United States in the field of education through the Fulbright scholarship has brought about the American Indonesian Exchange Foundation (AMINEF), making it one of the organizations that can participate in promoting Indonesian culture and language to the United States through its programs. AMINEF-Fulbright manages partnerships and funding from various sectors to develop skills in underdeveloped areas in Indonesia. This organization serves as an information bridge between the two countries through its excellent programs. This research uses a descriptive qualitative method that analyzes the efforts and roles of AMINEF-Fulbright as a binational organization in promoting Indonesian culture and language in the United States, which can be seen through its excellent programs such as Fulbright Foreign Language Teaching Assistant (FLTA), Community College Initiative Program (CCIP), US Student Researcher, and others. The study shows that AMINEF-Fulbright has become a strong driver for promoting cross-cultural understanding and appreciation of different cultures from both countries. This organization can be a significant actor in promoting Indonesian culture and language to the United States.